Digital Educational Technologies in Gifted STEAM Education: A Qualitative Case Study of Teachers’ Perceptions and Practices in a Mixed-Ability Learning Context - Emmanouil D. Milakis; Constantina Corazon Argyrakou; Eleni Chantzouli (Sagamedia Teknologi Nusantara, 2026)
This qualitative case study examines how teachers perceive and implement digital educational technologies in Gifted STEAM Education within a mixed-ability learning context involving gifted and non-gifted students. The study was situated in an annual professional development program on Gifted STEAM Education and involved six purposively selected teachers with experience in STEM/STEAM Education and/or Gifted Education. Data were collected through semi-structured interviews, mini focus groups, overt participant and non-participant observations, field notes, and textual documents, and were analysed using thematic analysis. The findings show that teachers viewed digital technologies not as neutral technical resources, but as pedagogical mediators that could shape inquiry, differentiation, participation, and creative production. Meaningful technology integration required explicit digital skill objectives, structured guidance, and formative monitoring. Digital tools supported Gifted STEAM learning when they were connected to interdisciplinary inquiry, design activities, multimedia production, creative expression, and differentiated forms of participation. Equity was understood as a multidimensional concern involving device access, meaningful participation, differentiated support, role distribution, ethical use, data protection, and equivalent non-digital pathways. Implementation, however, was constrained by inadequate infrastructure, outdated equipment, software incompatibility, unstable internet access, time pressure, unequal access, and institutional ambiguity. The study contributes to the literature by clarifying how digital technologies can support inclusive differentiation, interdisciplinary integration, and ethical digital practice in Gifted STEAM Education. The findings should be interpreted in light of the small sample, the specific professional development context, the non-formal educational setting, and the limited transferability of a single qualitative case study.